THE MECHANISMS OF OVERSIGHT ON GOVERNMENT CONTRACTS IN IRAQ ANDITS IMPACT ON THE EFFECTIVENESS OF PUBLIC PROJECT IMPLEMENTATION (American Journal of Research in Humanities and Social Sciences, 2025)
The research aims to study the regulatory framework governing governmental contracts by analyzing the different levels of oversight: legislative (the Council of Representatives andits specialized committees), executive (ministries andcontracting authorities), judicial (courts andadministrative judicial bodies), andindependent bodies (the Federal Board of Supreme Audit andthe Integrity Commission), in addition to societal andmedia oversight. The study also reviews the applicable laws andregulations, such as the Government Contracts Implementation Instructions No. (2) of 2014, andcompares them with international standards in the field of governance andtransparency. The research adopts a descriptive-analytical methodology, based on a review of legal andeconomic literature, as well as an analysis of reports from the Federal Board of Supreme Audit andthe Integrity Commission, in addition to case studies of some stalled public projects. The study concludes that the multiplicity of oversight bodies contributes to uncovering violations andenhancing transparency, but at the same time creates institutional overlap andexcessive bureaucracy, which slow down contracting andimplementation procedures. It also shows that weak political will, lack of technical expertise in oversight bodies, andthe failure to activate preventive oversight constitute major obstacles to achieving effective control. The research recommends restructuring the oversight system on an integrative rather than competitive basis, activating preventive oversight through digitalization andthe introduction of electronic contract management systems, strengthening the independence of oversight bodies from political influence, developing the capacities of their staff, andinvolving civil society organizations andthe media as active actors in societal oversight to ensure the quality andeffectiveness of public project implementation.